2023
DOI: 10.3389/fimmu.2023.1207533
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body bioluminescence imaging of T-cell response in PDAC models

Abstract: IntroductionThe location of T-cells during tumor progression and treatment provides crucial information in predicting the response in vivo.MethodsHere, we investigated, using our bioluminescent, dual color, T-cell reporter mouse, termed TbiLuc, T-cell location and function during murine PDAC tumor growth and checkpoint blockade treatment with anti-PD-1 and anti-CTLA-4. Using this model, we could visualize T-cell location and function in the tumor and the surrounding tumor microenvironment longitudinally. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…These models combine the high sensitivity and real-time dynamics of bioluminescence for in vitro screening and in vivo imaging with the cellular resolution of lacZ or fluorescent reporters (Day et al, 1998;Contag et al, 2000). The everexpanding diversity of luciferin/luciferase systems provides the opportunity to visualise expression of more than one gene of interest in the same animal using luciferase proteins which either require different substrates for activation (Jones et al, 2017) or produce spectrally distinct luminescence signal (Mezzanotte et al, 2011;Gleneadie et al, 2023;McMorrow et al, 2023) (exemplified in Figure 1A, right-hand panel, red and green).…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…These models combine the high sensitivity and real-time dynamics of bioluminescence for in vitro screening and in vivo imaging with the cellular resolution of lacZ or fluorescent reporters (Day et al, 1998;Contag et al, 2000). The everexpanding diversity of luciferin/luciferase systems provides the opportunity to visualise expression of more than one gene of interest in the same animal using luciferase proteins which either require different substrates for activation (Jones et al, 2017) or produce spectrally distinct luminescence signal (Mezzanotte et al, 2011;Gleneadie et al, 2023;McMorrow et al, 2023) (exemplified in Figure 1A, right-hand panel, red and green).…”
Section: Figurementioning
confidence: 99%
“…Using this technique, even a single cell could be detected (Kim et al, 2010;Iwano et al, 2018), with a linear relationship between cell number and signal over 5 logarithmic scales (Contag et al, 2000;Rehemtulla et al, 2000). As the tumour progresses studies have suggested that the luciferase signal begins to plateau, likely due to ongoing necrosis and the low oxygen content in tumour cores (Soling et al, 2004;Jurczok et al, 2008;McMorrow et al, 2023). Bioluminescence has been used extensively for in vivo (O'Farrell et al, 2013;Manni et al, 2019;Alsawaftah et al, 2021) and in vitro (Wang et al, 2006;Badr et al, 2011;Blanquart et al, 2011;Improgo et al, 2011) cancer drug screening, often using the same bioluminescent cancer cell lines for each stage of the study (Qian et al, 2005;Wang et al, 2006;Wang et al, 2023).…”
Section: Tumorigenesismentioning
confidence: 99%
See 3 more Smart Citations